2021
DOI: 10.1038/s41598-021-87158-2
|View full text |Cite
|
Sign up to set email alerts
|

Digestive symptoms in daily life of chronic adrenal insufficiency patients are similar to irritable bowel syndrome symptoms

Abstract: Gastrointestinal symptoms are frequent in acute adrenal insufficiency. Although digestive symptoms can significantly reduce quality of life, they are rarely described in patients with treated chronic adrenal insufficiency (CAI). We aimed to characterize digestive symptoms in CAI patients. We used the section pertaining functional bowel disorders of the Rome IV questionnaire. A questionnaire was published on the website of the non-profit patient association “Adrenals” (NPPA of CAI patients) for five months. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Abdominal pain is one of the main clinical symptoms of adrenal insufficiency among other symptoms such as weakness, fatigue, anorexia, weight loss orthostatic hypotension and salt craving 37 . The nonspecific digestive symptoms, such as abdominal pain, sometimes lead to misdiagnosis of an acute abdomen 77 . These digestive manifestations are thought to be a direct consequence of glucocorticoid and mineralocorticoid deficiency, but the mechanism remains unclear 77 .…”
Section: Abdominal Pain Of Systemic Originmentioning
confidence: 99%
See 3 more Smart Citations
“…Abdominal pain is one of the main clinical symptoms of adrenal insufficiency among other symptoms such as weakness, fatigue, anorexia, weight loss orthostatic hypotension and salt craving 37 . The nonspecific digestive symptoms, such as abdominal pain, sometimes lead to misdiagnosis of an acute abdomen 77 . These digestive manifestations are thought to be a direct consequence of glucocorticoid and mineralocorticoid deficiency, but the mechanism remains unclear 77 .…”
Section: Abdominal Pain Of Systemic Originmentioning
confidence: 99%
“…The nonspecific digestive symptoms, such as abdominal pain, sometimes lead to misdiagnosis of an acute abdomen 77 . These digestive manifestations are thought to be a direct consequence of glucocorticoid and mineralocorticoid deficiency, but the mechanism remains unclear 77 . In a cross‐sectional controlled study of 119 patients with chronic adrenal insufficiency, 40% of the study population reported abdominal pain at least once a week during the previous 3 months 77 .…”
Section: Abdominal Pain Of Systemic Originmentioning
confidence: 99%
See 2 more Smart Citations
“…Part of the explanation could be the noradrenergic overstimulation, since the normal stress response is based on two pillars: the HPA-axis and the autonomic nervous system, of which only the first is deficient in AI, whereas the latter is intact (see Challenges in Current Treatment Strategies ) ( 35 ). Chronic gastrointestinal symptoms are more prevalent in AI patients compared to controls, being incapacitating and similar to symptoms of the irritable bowel syndrome in about 30% of patients ( 36 ). Diffuse limb and back pain are also frequently reported.…”
Section: Adrenal Crisis: the Most Serious And Life-threatening Manifestation Of Adrenal Insufficiencymentioning
confidence: 99%